High Organization-Based Self-Esteem Is Associated With Lower Risk of Depressive Symptoms Among University Athletes - Noguri, Ryusei; Kawata, Yujiro; Yamaguchi, Shinji; Shibata, Nobuto; Ota, Tsuneyoshi (Frontiers in Psychology, 2022)
As depressive symptoms can impair athletes’ healthy competitive life and lead to a decline in performance, it is necessary to identify and prevent these symptoms. Organization-based self-esteem is one of the factors that influence the mental health of the members of an organization. It has been found that employees with high organization-based self-esteem have good mental health. However, the relationship between organization-based self-esteem and mental health has not yet been investigated in athletes. Therefore, we aimed to develop an organization-based self-esteem scale for university athletes (Study I) and investigate the relationship beween organization-based self-esteem and depressive symptoms (Study II). Study I included subsample A: 210 university athletes (average age 19.6 ± 0.64 years) and subsample B: 371 university athletes (average age 19.4 ± 0.90), who responded to the newly developed Organization-Based Self-Esteem Scale for University Athletes (OBSE-UA), the Rosenberg Self-Esteem Scale, and the Sports Commitment Scale. To confirm the reliability of the developed scale, two weeks later they responded to the OBSE-UA again. In Study II, the participants were 232 university athletes (average age 19.5 ± 1.10 years), who completed the OBSE-UA developed in Study I and the Self-Rating Depression Scale. In Study I, we extracted a one-factor structure with six items for the OBSE-UA using exploratory and confirmatory factor analysis. Sufficient validity and reliability were confirmed by examining the relationship between organization-based self-esteem and sports commitment scale and retest methods, respectively. In Study II, athletes with high organization-based self-esteem showed a 0.33 time lower risk of experiencing depressive symptoms, compared to athletes with low organization-based self-esteem.